Tanzania's Growth Process and Success in Reducing Poverty - Treichel, Volker (IMF Working Papers; Working Paper ;, 2005)
Since 1995, Tanzania has made major progress in economic reform and macroeconomic stabilization, resulting in strong growth and low inflation. This paper reviews Tanzania's growth performance and prospects and assesses the impact of growth on poverty. It finds that growth has been increasingly driven by higher factor productivity and that a continuation of recent policies should allow Tanzania to grow above 5 percent a year over the medium term. Furthermore, it finds that growth since 1995 has resulted in a significant decline of poverty and that prospects are favorable for Tanzania to attain its objectives for reducing income poverty by 2015.